Effect Of Work Conflict, Work Load, And Work Environment On Employees Work Stress (Case Study At Pt Indoraya Internasional Di Yogyakarta) - FX Pudjo Wibowo; Mustofa Mustofa (Komunitas Dosen Indonesia, 2018)
This study aims to examine the effect of work conflict, workload and work environment on the work stress of employees at PT Indoraya Internasional in Yogyakarta. The independent variables in this study are work conflict, workload, and work environment while the dependent variable in this research is work stress. Data collection methods were used by distributing questionnaires directly to PT Indoraya International employees in Yogyakarta. The analytical method used in this study uses the analysis of the coefficient of determination, multiple regression analysis F test and t test, using SPSS Version 20.00 based on data from 100 respondents studied. The results showed that work conflict, workload and work environment simultaneously had a significant influence on employee work stress and partially work conflicts, workloads, and work environment had a significant effect on employee work stress.